Uveal Melanoma-Derived Extracellular Vesicles Display Transforming Potential and Carry Protein Cargo Involved in Metastatic Niche Preparation - Tsering, Thupten (Cancers (Basel), 2020)
SIMPLE SUMMARY: Uveal melanoma is a rare but deadly cancer that shows remarkable metastatic tropism to the liver. Extracellular vesicles (EVs) are nanometer-sized, lipid bilayer-membraned particles that are released from cells. In our study we used EVs derived from primary normal choroidal melanocytes and matched primary and metastatic uveal melanoma cell lines from a patient. Analysis of these EVs revealed important protein signatures that may be involved in tumorigenesis and metastatic dissemination. We have established a model to study EV functions and phenotypes which can be used in EV-based liquid biopsy. ABSTRACT: Extracellular vesicles (EVs) carry molecules derived from donor cells and are able to alter the properties of recipient cells. They are important players during the genesis and progression of tumors. Uveal melanoma (UM) is the most common primary intraocular tumor in adults and is associated with a high rate of metastasis, primarily to the liver. However, the mechanisms underlying this process are poorly understood. In the present study, we analyzed the oncogenic potential of UM-derived EVs and their protein signature. We isolated and characterized EVs from five UM cell lines and from normal choroidal melanocytes (NCMs). BRCA1-deficient fibroblasts (Fibro-BKO) were exposed to the EVs and analyzed for their growth in vitro and their reprograming potential in vivo following inoculation into NOD-SCID mice. Mass spectrometry of proteins from UM-EVs and NCM-EVs was performed to determine a protein signature that could elucidate potential key players in UM progression. In-depth analyses showed the presence of exosomal markers, and proteins involved in cell-cell and focal adhesion, endocytosis, and PI3K-Akt signaling pathway. Notably, we observed high expression levels of HSP90, HSP70 and integrin V in UM-EVs. Our data bring new evidence on the involvement of UM-EVs in cancer progression and metastasis.